2022
DOI: 10.1016/j.amsu.2021.103145
|View full text |Cite
|
Sign up to set email alerts
|

Can l-carnitine reduce post-COVID-19 fatigue?

Abstract: A significant number of patients infected with the new coronavirus suffer from chronic fatigue syndrome after COVID-19, and their symptoms may persist for months after the infection. Nevertheless, no particular treatment for post-disease fatigue has been found. At the same time, many clinical trials have shown the effectiveness of l -carnitine in relieving fatigue caused by the treatment of diseases such as cancer, MS, and many other diseases. Therefore, it can be considered as a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…This new virus is the seventh human coronavirus described to date as responsible for respiratory infections [ 2 ], and is classified into the beta coronavirus subgroup [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This new virus is the seventh human coronavirus described to date as responsible for respiratory infections [ 2 ], and is classified into the beta coronavirus subgroup [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the potential underlying mechanisms of ADEM in association with SARS-CoV-2 is the cytokine pathway activation, which is known to be involved in the pathology of ADEM. It has been stated to result from T cells affected by SARS-CoV-2 inducing a storm of cytokines, especially IL-6 [ [16] , [17] , [18] ]. This results in sequences of immune responses that may play an important role in the pathogenesis of ADEM [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intake of anticoagulants is known for increased risk of hematoma [ 8 , 9 ]. A few case studies have reported similar in severe COVID19 patients [ 10 ]. In this case series, we present COVID19 patients who were treated with anticoagulants and were seen to be presented with retroperitoneal hematoma.…”
Section: Introductionmentioning
confidence: 94%